A direct current conversion device for closed HTS coil of superconducting magnetic energy storage. (June 2023) - Li, Chao; Li, Gengyao; Xin, Ying; Li, Bin
Abstract: High-temperature superconducting (HTS) magnets are widely used in various fields because of their superior performance. However, the dc operating current of a closed HTS coil, after energization, cannot be adjusted flexibly and efficiently, which limits the application scenarios of HTS magnets. Besides, the joint resistance within HTS magnets will cause obvious decay of operating current, which seriously impacts the performance. In this work, a novel dc conversion device using variable superconducting inductor is proposed, which can effectively step up and step down the dc operating current of closed HTS coils. An experimental prototype was designed and built. Experimental results show the proposed dc conversion device can tune the operating current of the closed HTS coil in a wide range with little power loss. Simulation tests are carried out to explore further working details and application potential of the proposed device. Apart from adjusting the operating current, the proposed dc conversion device could also serve to compensate field decay of the HTS magnets caused by joint resistance or external field. Highlights: A novel direct current conversion device for closed HTS coil of superconducting magnetic energy storage is proposed. The working principle of the proposed device has been analyzed from the perspective of electromagnetism and energy. Experiments have been carried out to display its working performance and verify the correctness of the working principle. A simulation model based on finite element method is built to explore further working details.